ANALISIS FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP AUDIT DELAY (Jurnal Ekonomi : Journal of Economic, 2022)
Audit delay is the time for completion of the audit which is measured from the end of the fiscal year until the date the audit report is issued, a long audit delay will affect the timeliness of the delivery of financial statements. This study aims to see the effect of financial distress, auditor switching and the size of mining companies listed on the Indonesia Stock Exchange for the 2014-2018 period. The sample of this research is 35 mining sector companies with a period of 5 years, the sampling technique uses purposive sampling technique, so that the sample obtained is 190. The research method uses multiple linear regression analysis with the F test and t test.The results showed that simultaneously financial distress, auditor switching and company size have an effect on audit delay, but only partially financial distress has a significant positive effect on audit delay, while auditor switching and company size have no effect on audit delay. The findings in this study, that the average audit delay time for mining companies is 98 days.Keywords: financial distress, auditor switching, company size, audit delay